A comparative analysis of experts' judgment methods for patient safety implementation - FMEA and fuzzy AHP. (3rd November 2022) - Golrizgashti, Seyedehfatemeh; Keshmiri, Mehrdad; Nazabadi, Noshad
Regards to the complexity of healthcare systems, it is very important to apply accurate and effective methods to manage probable risks to enhance patient safety. The aim of this study is to identify probable risks by using failure modes, effects analysis method and fuzzy analytic hierarchy process to compare obtained results and define shortages of experts' judgment methods. This study has been conducted in electrocautery surgery in an operating room at a hospital in Iran. The failures modes, their effects and causes are identified by in-depth interviews, hospital documentation and fuzzy Delphi method. Obtained results show that decision making based on experts' judgment methods may lead to different results, therefore applying accurate quantitative methods to enhance reliability and patients' safety is essential. While this study identifies the potential risks of a complex surgery, comparing the obtained results based on two methods is the most important contribution of this paper.